2015
DOI: 10.1186/s12955-015-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

A web-based psychological support program for caregivers of children with cystic fibrosis: a pilot study

Abstract: BackgroundParents caring for a child with Cystic Fibrosis (CF) are at high risk for psychological distress and have limited access to psychological care. Therefore, a web-based psychological support program for severely distressed parents of children with CF (WEP-CARE) was developed and evaluated for its feasibility and efficacy.MethodsA clinical expert panel developed WEP-CARE based on principles of cognitive-behavioral therapy. This web-based writing therapy comprises nine sessions, tailored for the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
(45 reference statements)
3
21
0
2
Order By: Relevance
“…The encephalopathies or neuromuscular disorder, as well as cystic fibrosis, are disease that lead to a significant deterioration of quality of life both in patients (Pé ntek et al 2014; Fidika et al 2015, Smith Grzvwacz 2014. How parents cope with the burden of caring for a chronically ill child depends on various factors: contextual psychological, cultural, emotional, social.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…The encephalopathies or neuromuscular disorder, as well as cystic fibrosis, are disease that lead to a significant deterioration of quality of life both in patients (Pé ntek et al 2014; Fidika et al 2015, Smith Grzvwacz 2014. How parents cope with the burden of caring for a chronically ill child depends on various factors: contextual psychological, cultural, emotional, social.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Another similar study examining the impact of e-learning is a study in which efeedback to parents helped children grow and reduce their obesity (16). Also web-based and electronic support for parents of children with cystic fibrosis have also led to reduced anxiety and depression and improved quality of life in parents (15); And e-learning for adolescents aged 11 to 14 with diabetes led to increased quality of life and decreased HbA1c (Hemoglobin A1c) in them (13).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the studies, Internet-based psychosocial education interventions have been effective for a wide range of populations with physical and psychiatric problems, including the PTSD population and parents of children with trauma; In parents and children (8), Prevents stable and chronic PTSD in children (14). In addition, the provision of an Internet-based psychological support program for caregivers of children with cystic fibrosis has shown reduced anxiety and depression and improved parental quality of life (15). In another study, intervention using Internet feedback has been shown to improve children's growth and reduce their obesity (16).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Swallow et al, [4] described that parents of children with CKD want continuously available, accessible and reliable support. Although in recent years more and more online support programs for parents of children with chronic diseases, such as diabetes mellitus [5,6], cystic fibrosis [7,8] and asthma [9] have been developed, online support programs for parents of children with CKD are lacking.…”
Section: Introductionmentioning
confidence: 99%